M.C. Escher : the graphic work - Escher, M. C. (Maurits Cornelis), 1898-1972. (Los Angeles : Taschen, 2001)
A collection of woodcuts and lithographs by twentieth-century graphic artist M.C. Escher.
Translation of: M.C. Escher: Grafiek enTekeningen.
Includes bibliographical references (p. 196).
Adult
Keywords: Escher, M. C., -- 1898-1972 -- Catalogs; Escher, M. C., -- 1898-1972 -- Catalogs; Artists -- Netherlands -- History and criticism; Artists -- Netherlands -- History and criticism